2014
DOI: 10.1038/jid.2013.293
|View full text |Cite
|
Sign up to set email alerts
|

A Conditional Zebrafish MITF Mutation Reveals MITF Levels Are Critical for Melanoma Promotion vs. Regression In Vivo

Abstract: The microphthalmia-associated transcription factor (MITF) is the “master melanocyte transcription factor” with a complex role in melanoma. MITF protein levels vary between and within clinical specimens, and amplifications and gain- and loss-of-function mutations have been identified in melanoma. How MITF functions in melanoma development and the effects of targeting MITF in vivo are unknown because MITF levels have not been directly tested in a genetic animal model. Here, we use a temperature-sensitive mitf ze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 37 publications
2
76
0
Order By: Relevance
“…Moreover, we found eight candidate loci conferring resistance to PLX4720 treatment. Interestingly, both lists contained Mitf, which is a well-known melanoma oncogene amplified in ∼10% of primary and ∼20% of metastatic melanomas (35,52,53) and has been described as a mediator of drug resistance in melanoma (35-37, 54, 55).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found eight candidate loci conferring resistance to PLX4720 treatment. Interestingly, both lists contained Mitf, which is a well-known melanoma oncogene amplified in ∼10% of primary and ∼20% of metastatic melanomas (35,52,53) and has been described as a mediator of drug resistance in melanoma (35-37, 54, 55).…”
Section: Discussionmentioning
confidence: 99%
“…42,43 Other factors that can induce melanoma regression include decreased microphthalmia transcription factor activity within melanocytes. 44 Another mechanism, proposed by Bastian,45 suggests that decreased telomerase activity can lead to abnormal telomere function, and thus induce replicative senescence in melanoma cells, resulting in the generation of apoptotic bodies and a T lymphocyte response.…”
Section: Spontaneous Regression In Melanomamentioning
confidence: 99%
“…Utilizing this mitfa temperature sensitive allele, we found that lowered levels of MITF activity cooperated with BRAF V600E mutations to promote nevi and melanoma in vivo, and that loss of MITF in established melanomas led to rapid melanoma regression ( Fig. 2A and B) (20). Furthermore, while melanoma incidence was similar in BRAF V600E p53 and BRAF V600E mitf fish, the histopathology of the melanomas were strikingly different.…”
Section: Mitf Is Mutated and Amplified In Melanoma And Is A Melanomamentioning
confidence: 91%
“…2C and D). An important implication from this animal model is the validation of MITF as a drug target in melanoma, but also that caution would be needed in this approach, because insufficient targeting of MITF activity (leading to simply a reduction in MITF activity) could be oncogenic (20).…”
Section: Mitf Is Mutated and Amplified In Melanoma And Is A Melanomamentioning
confidence: 99%